Socialization of Professional Zakat as An Effort to Raise Awareness of The Community Alms of Nitikan Village, Sorosutan Village, Umbulharjo District, Special Region of Yogyakarta - Ayik Khusnul Khotimah; Shobihatun Nada Rofifah; Hamadan Rosyiddani; Neni Nurkholisah; Muhammad Farkhan Nur Radifan; Afifah Afifah; Alifia Nur Afifah; Rahmat Alvindi; Muhammad Iqbal Ghifary; Ghilmal Faiz Zakiya; Khafid Akbar Faozi; Anton Qurniawan; Septigung Prabawantari (Journal of Islamic Economy and Community Engagement, 2020)
Community service activities are carried out by holding socialization on the importance of giving alms to women PKK (Family Welfare Empowerment) in Nitikan Village, Umbulharjo District, Yogyakarta City. This activity aims to increase public awareness and understanding of zakat payment. This activity takes the form of socialization using lecture and question and answer methods. The material consists of the definition of zakat, ashnaf zakat, zakat payment methods and case examples. The participants of the socialization consisted of 20 PKK (Family Welfare Empowerment) mothers in Nitikan village, 1 student from Widya Mataram University, and 1 student from Sarjanawiyata Tamansiswa University.Keywords: Zakat, awareness, understanding, society.